Pelatihan Pengelolaan Keuangan dan Penerapan SEOJK pada PT BPR Mojosari Pahalapakto untuk Optimalisasi Operasional Keuangan Perbankan - Syaiful Akbar, Fajar; Rahmawati, Dyah; Priono, Hero (Fakultas Ekonomi Universitas Islam Majapahit, 2024)
An understanding of accounting systems and financial reports is required by entities and institutions that distribute productive credit. For entities, accounting systems are useful for processing financial transactions and presenting financial information in the form of financial reports. Meanwhile, the use of accounting systems and financial reports for institutions that distribute productive credit is to assess the financial position, performance and cash flow turnover of prospective customers in the credit distribution process. In this way, it is hoped that the credit distributed can be used according to the objectives so that it can improve the financial performance of prospective customers. In this case, the financial management regulated in the 2023 SEOJK also requires companies, in this case BPR, to adjust to the start-up that applies in the midst of unstable economic conditions after Covid-19, so that this training helps BPR M, Ojosari Pahalapakto personnel to be able to apply the regulations. which has been determined by the OJK.